Epidemiology in mixed host populations - Mundt, C. C.; Garrett, Karen A. (My University, 2007)
Although plant disease epidemiology has focused on populations in which all host plants have the same genotype, mixtures of host genotypes are more typical of natural populations and offer promising options for deployment of resistance genes in agriculture. In this review, we discuss Leonard's classic model of the effects of host genotype diversity on disease and its predictions of disease level based on the proportion of susceptible host tissue. As a refinement to Leonard's model, the spatial structure of host and pathogen population can be taken into account by considering factors such as autoinfection, interaction between host size and pathogen dispersal gradients, lesion expansion, and host carrying capacity for disease. The genetic composition of the host population also can be taken into account by considering differences in race-specific resistance among host genotypes, compensation, plant competition, and competitive interactions among pathogen genotypes. The magnitude of host-diversity effects for particular host-pathogen systems can be predicted by considering how the inherent characteristics of a system causes it to differ from the assumptions of the classic model. Because of the limited number of studies comparing host-diversity effects in different systems, it is difficult at this point to make more than qualitative predictions. Environmental conditions and management decisions also influence host-diversity effects on disease through their effect on factors such as host density and epidemic length and intensity.
Citation: Garrett, K., and Mundt, C. (2007). Epidemiology in Mixed Host Populations. Phytopathology, 89(11), 984-990. https://doi.org/10.1094/PHYTO.1999.89.11.984
Keywords: Epidemiology; Mixed host populations; Variety mixtures; Cultivar mixtures; Genetic diversity